Empowering farmers to increase the participation in the sustainable food yard program in Tegalrejo Village, Yogyakarta City - Muhammad Iqbal Ar Ryyadh; Siti Nurlaela; Endah Puspitojati (Universitas Muhammadiyah Magelang, 2023)
The purpose of this community service is to develop a design for empowering farmers in order to increase their participation in the Sustainable Food Yard Program (P2L). Activities carried out from January to July 2022. The method used in this activity is extension and training to local farmers. Training on plant maintenance from plant-based pests and diseases aims to increase farmers' knowledge, attitudes and skills, especially related to P2L. The results of the study show that age, non-formal education, farming experience, group roles, availability of facilities, extension extension support, and government support simultaneously have a significant effect on farmer participation in the use of home gardens. Partially, non-formal education and extension support have a significant effect on farmer participation in the use of home gardens in Tegalrejo Village, Tegalrejo Kemantren, Yogyakarta City.